Improvement of the drug encapsulation into biodegradable polyester nanocarriers by blending of poly(lactic-co-glycolic acid) and polycaprolactone - Ágnes Ábrahám; Gergő Gyulai; Tünde Tóth; Barna Szvoboda; Judith Mihály; Ákos Szabó; Éva Kiss (eXPRESS Polymer Letters)
Biocompatible and biodegradable polymers such as poly(lactic-co-glycolic acid), PLGA and polycaprolactone, PCL nanoparticles (NPs) have been used successfully as drug carriers in controlled drug release. The main weakness is the generally low drug loading (1–-5%) of the NPs. An option to enhance the drug content of NPs is to find the optimum matrix for a given drug molecule. To reveal the influence of matrix and drug polarity on the favoured encapsulation, polymeric NPs loaded with a series of alkyl-4-hydroxybenzoate (paraben) with increasing alkyl chain length (C1-C8) as model drugs were prepared by nanoprecipitation method. The paraben series represents the drugs with various polarities while the selected matrix polymers show increased hydrophobicity: PLGA with 50% lactic acid content (PLGA50) < PLGA with 75% lactic acid content (PLGA75) < PCL. The drug content of the PLGA NPs was found to significantly increase up to 10% with the hydrophobicity of the parabens, while encapsulation was further boosted by applying PCL. To find the proper fit between drug and matrix and finely tune the polarity of the NPs, as a novel approach, blends of PLGA50 and PCL were applied as matrix polymers. The drug loading of the NPs was proved to be dependent on the systematically changed blend composition. Furthermore, the introduction of PCL into the PLGA50 matrix improves the release kinetics of the active component.